2019
DOI: 10.3390/atmos10030103
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Particulate Matter Pollution and Acute Coronary Syndrome Incidence

Abstract: (1) Background: In recent decades, studies have reported on the increased cardiovascular risk associated with increased levels of air pollutants, especially particulate matters (PM). It remains unclear whether the specific subgroups share the same involvement and whether the effect is delayed. (2) Methods: Data for acute coronary syndrome (ACS) incidences from 2008 to 2011 were gathered in two major medical centres in Slovenia. A time series analysis was conducted in which daily ACS incidence data were linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Of these, it is greatly important to address air pollution issues where reducing air pollution will meet the Sustainable Development Goals (SDG) proposed by the United Nation (UN) in SDG 3, for good health and well-being [ 5 ]. Increased PM from air pollution contributes to the occurrence of acute coronary syndrome (ACS) in several studies [ 6 ]. MicroRNAs (miRNAs), a short noncoding RNA, have been observed in few studies to be dysregulated in inflammatory modulation in cardiovascular disorder exposed to PM [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, it is greatly important to address air pollution issues where reducing air pollution will meet the Sustainable Development Goals (SDG) proposed by the United Nation (UN) in SDG 3, for good health and well-being [ 5 ]. Increased PM from air pollution contributes to the occurrence of acute coronary syndrome (ACS) in several studies [ 6 ]. MicroRNAs (miRNAs), a short noncoding RNA, have been observed in few studies to be dysregulated in inflammatory modulation in cardiovascular disorder exposed to PM [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Study from ninety largest cities in the United States by the National Morbidity, Mortality, and Air Pollution Study (NMMAPS) observed that cardiopulmonary-related mortality rose by the increment of PM 10 within a 24-hour period [ 25 ]. In another study, daily concentration of PM 10 was significantly having an impact on ACS incidence, higher on elderly with the highest impact on older men [ 6 ]. Moreover, increase in PM 10 pollution was noted to have relation to rise in frequency of percutaneous coronary interventions (PCIs) in ACS patients [ 26 ].…”
Section: Introductionmentioning
confidence: 99%